Peran Kesatuan Pekerja dan Pelaut Perikanan (KP3I) dalam Meningkatkan Kompetensi SDM Awak Kapal Perikanan Domestik - Imron Natsir; Nuratmojo Nuratmojo; Sumardi Sumardi; Muhammad Husni; Sony Permadi (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The Indonesian Fisheries Workers and Seafarers Union (KP3I) has a significant role to play in improving the human resource competence (HRM) of the crew of domestic fishing vessels. This article examines the various challenges faced by fishing crews, including lack of training and education, inadequate working conditions, and economic and social uncertainty. KP3I plays a role through the conduct of comprehensive training and education programmes, advocacy and protection of labour rights, as well as collaboration with governments and related agencies. Case studies show that the program has successfully improved the efficiency and well-being of workers, which contributes to increased productivity and competitiveness of the national fishing industry.Strategic recommendations for sustainable competence development include support from governments and the private sector, as well as the promotion of education and training.